Romidepsin Promotes Osteogenic and Adipocytic Differentiation of Human Mesenchymal Stem Cells through Inhibition of Histondeacetylase Activity. (14th March 2018) - Ali, Dalia; Chalisserry, Elna P.; Manikandan, Muthurangan; Hamam, Rimi; Alfayez, Musaad; Kassem, Moustapha; Aldahmash, Abdullah; Alajez, Nehad M.
Abstract : Bone marrow mesenchymal stem cells (BMSCs) are adult multipotent stem cells that can differentiate into mesodermal lineage cells, including adipocytes and osteoblasts. However, the epigenetic mechanisms governing the lineage-specific commitment of BMSCs into adipocytes or osteoblasts are under investigation. Herein, we investigated the epigenetic effect of romidepsin, a small molecule dual inhibitor targeting HDAC1 and HDAC2 identified through an epigenetic library functional screen. BMSCs exposed to romidepsin (5 nM) exhibited enhanced adipocytic and osteoblastic differentiation. Global gene expression and signaling pathway analyses of differentially expressed genes revealed a strong enrichment of genes involved in adipogenesis and osteogenesis in romidepsin-treated BMSCs during induction into adipocytes or osteoblasts, respectively. Pharmacological inhibition of FAK signaling during adipogenesis or inhibition of FAK or TGF β signaling during osteogenesis diminished the biological effects of romidepsin on BMSCs. The results of chromatin immunoprecipitation combined with quantitative polymerase chain reaction indicated a significant increase in H3K9Ac epigenetic markers in the promoter regions of peroxisome proliferator-activated receptor gamma (PPAR γ ) and KLF15 (related to adipogenesis) or SP7 (Osterix) and alkaline phosphatase (ALP) (related to osteogenesis) in romidepsin-treated BMSCs. Our data indicated that romidepsin is a novel in vitro modulator of adipocytic and osteoblastic differentiation of BMSCs.